Climate risk and the nexus of clean energy and technology stocks - Elie Bouri; Tom L. Dudda; Lavinia Rognone; Thomas Walther (Annals of Operations Research, 2023)
We examine the impact of climate risks on the nexus of clean energy and technology stocks using a time-varying correlation model. We find that physical and transition climate risks are positively associated with the long-term correlation between clean energy and technology stock indices, whereas the effect of transition risk is more robust to different sample periods and alternative stock indices. On the contrary, the short-term correlation tends to decrease after shocks to physical risk, since clean energy stocks react more strongly to physical risk shocks than technology stocks.
Keywords: G10; Q42; Q54; Q55; 000; Climate risk; Clean energy; Technology stocks; Energy transition